Counterfinality: On the Increased Perceived Instrumentality of Means to a Goal - Schumpe, Birga M.; Bélanger, Jocelyn J.; Dugas, Michelle; Erb, Hans-Peter; Kruglanski, Arie W. (Frontiers in Psychology, 2018)
The present research investigates the counterfinality effect, whereby the more a means is perceived as detrimental to an alternative goal, the more it is perceived as instrumental to its focal goal. The results from five studies supported this hypothesis. Study 1 demonstrated the counterfinality effect in an applied context: The more pain people experienced when getting tattooed, the more they perceived getting tattooed as instrumental to attaining their idiosyncratic goals (being unique, showing off, etc.). Study 2 experimentally replicated and extended the results of Study 1: A counterfinal (vs. non-counterfinal) consumer product was perceived as more detrimental, which in turn predicted the perceived effectiveness of the product. In Studies 3 and 5, we showed that increased perceived instrumentality due to counterfinality led to more positive attitudes toward a means. Finally, Studies 4 and 5 indicated that simultaneous commitment to both the focal and the alternative goal moderated the counterfinality effect. We discuss how various psychological phenomena can be subsumed under the general framework of counterfinality, which has broad practical implications extending to consumer behavior, health psychology, and terrorism.